2003
DOI: 10.1520/jfs2002253
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Eight Dental Age Estimation Methods for Adults

Abstract: This paper evaluates the reliability and validity of eight published dental age estimation methods for adults that may aid in victim identification. Age was calculated on 20 Caucasian teeth of known age according to the methods of Kvaal (for in situ and extracted teeth), Solheim (for in situ and sectioned teeth), Lamendin (for extracted teeth), Johanson (for sectioned teeth) and Bang (for extracted and sectioned teeth) by one independent observer. For each method, mean age error and standard error were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 7 publications
2
39
0
2
Order By: Relevance
“…For males with more than 60 years were obtained equal results in the ranges -4 to -6 years and -7 to -9 years of underestimated age (9%). The Bang and Ramm has a tendency to overestimate the age when we analyzed teeth from young adults and underestimate age in the group of older age [16]. In our research project we obtained for Portuguese population the same results.…”
Section: Graphicsupporting
confidence: 69%
See 1 more Smart Citation
“…For males with more than 60 years were obtained equal results in the ranges -4 to -6 years and -7 to -9 years of underestimated age (9%). The Bang and Ramm has a tendency to overestimate the age when we analyzed teeth from young adults and underestimate age in the group of older age [16]. In our research project we obtained for Portuguese population the same results.…”
Section: Graphicsupporting
confidence: 69%
“…The Pearson correlation coefficient (0.86) as well as the coefficient of determination (0.74) for the adult Portuguese population allows us to conclude that the direct method for sectioned teeth gives the better relationship between the real age and the estimated age than radiograph method. The original Bang and Ramm method for sectioned teeth presented an average for standard deviation of 10.87 years [16]. In our research study, for all assessed methods, the standard deviation was lesser.…”
Section: Averagementioning
confidence: 47%
“…It is well recognized that in the sub-adult estimation of the age of subject, deceased or not may be attempted by examination of the maturation of the primary and permanent dentition [21]. There are dozens of published papers on age determination.…”
Section: Age Determination and Dental Radiologymentioning
confidence: 99%
“…However, neither will wholly replace the clinical judgment of a competent practitionerwhatever the discipline. In a study evaluating the accuracy of age determination [21] it was found that a study in which a practitioner made an educated guess of the age of the deceased was more accurate than more ''sophisticated'' technical methods. Solheim and Sundnes performed age estimation very well using a relatively simple visual assessment [30].…”
Section: Contemplating Human Judgmentmentioning
confidence: 99%
“…The amount of cementum on the root surface increases throughout the life of the individual and usually triples between the ages of 11 and 76 years [10]. Periodontal recession describe how much the roots of the teeth are exposed due to receding gums and is measured in millimetres (mm) by examining retraction of gums from root surface [11]. Root colour measures the degree of discoloration of the teeth which is related to increase in age ranging from a score of 1 referring to teeth with mild or no discoloration to a score of 5 referring to severely discoloured teeth [8].…”
Section: The Datamentioning
confidence: 99%